Motorcycle Related Injuries among Rural Dwellers in Irrua, Nigeria: Characteristics and Correlates - Dongo, A. E.; Kesieme, E. B.; Eighemherio, A.; Nwokike, O.; Esezobor, E.; Alufohai, E. (Emergency Medicine International, 2013)
Background. The escalating use of motorcycle for commercial transportation of commuters and goods has resulted in an increase in morbidity and mortality from road traffic injuries. Objectives. To study the characteristics of motorcycle injuries seen in Irrua, Nigeria. Materials and Methods. This is a one-year prospective study of all patients seen from January 1, 2009, to December 31, 2009. A structured proforma was filled for all consecutive crash victims involving a motorcycle. Results. Motorcycle injuries accounted for 11.6% of attendance in surgical emergency room (142 out of 1,214); 76.8% were males. Amongst victims 47.1% were riders, 42.9%, passengers, and 7.8% pedestrians. Extremity injury accounted for 42.2% while head injury occurred in 21.8%. There were 9 deaths (6.3%). In this study no victim used crash helmet. Conclusion. Banning of motorcycle for commercial use and the introduction of tricycles into rural/suburban comminutes may be an important preventive strategy.